PENGEMBANGAN MEDIA PEMBELAJARAN POWERPOINT INTERAKTIF PADA MATA PELAJARAN IPAS MATERI ENERGI TERBARUKAN UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV UPTD SDI NUNBAUN DELHA - Januario Jacsem Molum; Fembriani; Vera R. Bulu (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The research entitled "Development of Interactive Powerpoint Learning Media in the Science Subject of Renewable Energy Material to Improve the Learning Outcomes of Fourth Grade Students of UPTD SDI Nunbaun Delha" focuses on the development of Interactive PowerPoint media on Renewable Energy material, which is motivated by the low learning achievement of fourth grade students of UPTD SDI Nunbaun Delha in the 2025/2026 academic year. Using the Research and Development (R&D) method with the ADDIE model, this study aims to produce valid, practical, and effective media. The trial was conducted on 78 students through a Quasi-Experimental design of the Non-equivalent Control Group type. Data were collected through expert validation, student response questionnaires, and learning outcome test instruments. The research findings confirm that this media meets the validity criteria of 89.40% (Very Valid) and a practicality level of 87.36% (Very Practical). Statistical analysis showed a significance value of 0.000 < 0.05, thus concluding that this interactive PowerPoint media is highly feasible and effective in boosting student learning outcomes in science subjects.